Linguistoculture Features of Toponyms in the Epistles “Nurali Va Semurg” and “Turkman Dahosi or Makhtumkuli” - Abatov Doston Ruzimurod ugli (American Journal of Biodiversity, 2026)
This article analyzes toponyms with topomorphic codes (Shom, Karshi, Artak); color-denoting codes (Kyziloyak, Karakum, Sargai ota); attributive codes (Shirinbuloq); ethnomorphic codes (Yovmit, Goklang, Gozoyakli, Kalmyk land); anthropomorphic codes (Malik steppe, Shergozi madrasah, Idris Baba madrasah), and mytho theonym codes (Kohi Qaf, Khidir) used in Kashkadarya folk epics such as "Nurali and Semurg", "Turkman dahosi or Makhtumkuli" from a linguocultural perspective. At the end of the article, it is argued that by studying toponyms from a linguocultural perspective, it is possible to draw clear and correct conclusions about the history of the people to whom they belong, their lifestyle, customs, traditions and values, in general, their culture and its reflection in the language.